LIST OF CURRENTLY INCURABLE DISEASES - Yuldasheva Khusnora Khusinboy kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  article  examines  the  category  of  currently  incurable  diseases through  a  clinically  serious  and  analytically  cautious  lens.  In  medical  usage,  an incurable  disease  is  not  a  condition  for  which  nothing  can  be  done;  rather,  it  is  a condition  for  which  no  definitive  curative  therapy  has  yet  been  established,  even though symptom control, slowing of progression, life prolongation, and quality-of-life improvement may all be possible. The article focuses on six major examples that are widely recognized by authoritative health institutions as lacking a current cure: HIV infection,  Alzheimer’s  disease,  Parkinson’s  disease,  Huntington’s  disease, amyotrophic lateral sclerosis, and type 1 diabetes.